2018
DOI: 10.1093/hmg/ddy130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative methylome analysis of ICF patients identifies heterochromatin loci that require ZBTB24, CDCA7 and HELLS for their methylated state

Abstract: Alterations of DNA methylation landscapes and machinery are a hallmark of many human diseases. A prominent case is the ICF syndrome, a rare autosomal recessive immunological/neurological disorder diagnosed by the loss of DNA methylation at (peri)centromeric repeats and its associated chromosomal instability. It is caused by mutations in the de novo DNA methyltransferase DNMT3B in about half of the patients (ICF1). In the remainder, the striking identification of mutations in factors devoid of DNA methyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 83 publications
11
93
0
1
Order By: Relevance
“…ZBTB24, CDCA7 and HELLS could indeed be involved in the recruitment of DNMT3B at pericentromeric repeats, whose hypomethylation is a hallmark of all ICF patients. In contrast, DNA hypomethylation at germ line gene promoters and subtelomeric repeats is a signature of ICF1, and is not altered in ICF2‐4 patients, suggesting that ZBTB24, CDCA7 and HELLS are not required to direct DNMT3B to these regions. In fact, the transcriptional repressor E2F6 was shown to be required for DNMT3B recruitment at a subset of germ line gene promoters and maintenance of their methylated state although no mutation in this factor could be found in ICF patients …”
Section: Mutations In Chromatin Modifiers or Transcription Factors: Dmentioning
confidence: 96%
See 2 more Smart Citations
“…ZBTB24, CDCA7 and HELLS could indeed be involved in the recruitment of DNMT3B at pericentromeric repeats, whose hypomethylation is a hallmark of all ICF patients. In contrast, DNA hypomethylation at germ line gene promoters and subtelomeric repeats is a signature of ICF1, and is not altered in ICF2‐4 patients, suggesting that ZBTB24, CDCA7 and HELLS are not required to direct DNMT3B to these regions. In fact, the transcriptional repressor E2F6 was shown to be required for DNMT3B recruitment at a subset of germ line gene promoters and maintenance of their methylated state although no mutation in this factor could be found in ICF patients …”
Section: Mutations In Chromatin Modifiers or Transcription Factors: Dmentioning
confidence: 96%
“…Characterization of DNAme defects in ICF patients shows that, in addition to Sat‐2 and Sat‐3 repeats, reduced DNAme markedly affects non‐satellite NBL2 (now called SST1) and D4Z4 DNA repeats, subtelomeric regions, CpG islands of the inactive X chromosome in females, and a subset of germ line gene promoters . Hypomethylation of these germ line genes, which are maintained silent in all normal somatic cells, represents a specific pathological signature of DNMT3B dysfunction that could serve as a powerful biomarker for diagnosis, although the extent of its contribution to disease phenotype is unclear .…”
Section: Mutations In Dna Methyltransferases: Direct Impact On Dna Mementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in CDCA7 have been shown to cause ICF, a rare primary immunodeficiency characterized by epigenetic abnormalities (Thijssen et al, 2015). Previous research showed that CDCA7-mutated ICF patients show decreased DNA methylation levels at pericentromeric repeats and heterochromatin regions and, similarly, CDCA7 depletion in mouse embryonic fibroblasts leads to decreased DNA methylation at centromeric repeats (Thijssen et al, 2015;Velasco et al, 2018). In line with this we found that increased expression of CDCA7 is associated with increased methylation levels at 79 CpG-sites that were distributed across chromosomes (figure 4a) and were enriched in low-activity regions (e.g.…”
Section: Cdca7mentioning
confidence: 99%
“…Recessive mutations in ZBTB24 cause Immunodeficiency, Centromeric instability, Facial anomalies (ICF) syndrome (de Greef et al 2011;Cerbone et al 2012;Nitta et al 2013), a disorder characterized by hypomethylation of repetitive DNA . Aberrant DNA methylation has been reported in ICF patients carrying ZBTB24 nonsense mutations (Velasco et al 2018), upon shRNA-mediated ZBTB24 depletion in HCT116 cells, a human colon cancer cell line (Thompson et al 2018), and in a zebrafish zbtb24 knock out model (Rajshekar et al 2018). A combined function of ZBTB24 and DNMT3B has been suggested for mediating some gene body methylation in HCT116 cells (Thompson et al 2018), but the mechanisms by which ZBTB24 influences DNA methylation at other genomic regions remain unclear.…”
Section: Introductionmentioning
confidence: 99%